Comparative Genomic Analysis Reveals the Potential Risk of Vibrio parahaemolyticus Isolated From Ready-To-Eat Foods in China - Pang, Rui; Xie, Tengfei; Wu, Qingping; Li, Yanping; Lei, Tao; Zhang, Jumei; Ding, Yu; Wang, Juan; Xue, Liang; Chen, Moutong; Wei, Xianhu; Zhang, Youxiong; et al. (Frontiers in Microbiology, 2019)
Vibrio parahaemolyticus is a major foodborne pathogen associated with the consumption of aquatic products. The presence of this bacterium in ready-to-eat (RTE) foods has recently been reported. However, the genomic features and potential risks of V. parahaemolyticus isolated from RTE foods are poorly understood. To help understand the genome-wide characteristics of RTE food isolates, the complete genomes of 27 RTE food isolates were sequenced and compared to those of 20 clinical and 19 other environmental (e.g. water and aquatic product source) isolates using a comparative genomics approach. Analysis revealed that V. parahaemolyticus RTE food isolates had higher numbers of genes on average and possessed more accessory genes than isolates from other sources. Most RTE food isolates were positive for some known virulence-associated genes and pathogenicity islands (PAIs), and some of these isolates were genetically homologous to clinical isolates. Genome-wide association analysis revealed 79 accessory genes and 78 missense single-nucleotide polymorphisms that affected 11 protein-coding genes were significantly associated with RTE food sources. These genes were mostly involved in defense mechanisms and energy production and conversion according to functional annotation in the COG database. KEGG Pathway analysis showed that these genes mainly affected the biofilm formation of V. parahaemolyticus, and subsequent experiments confirmed that nearly all RTE food isolates possessed the ability to form biofilm. The biofilm formation can facilitate the persistence of V. parahaemolyticus in RTE foods, and the presence of virulence-associated genes poses a pathogenic potential to humans. Our findings highlight the potential risk of V. parahaemolyticus in Chinese RTE foods and illustrate the genomic basis for the persistence of these isolates. This study will aid in re-evaluating the food safety threats conferred by this bacterium.